Measures to overcome population decline and regional extinction crises of pan-tourism aspects in Korea: An exploratory study using ChatGPT - Hagchin Han; Jiangmin Ding (Global Business & Finance Review (GBFR), 2024)
Purpose: The issue of regional extinction due to the population crisis has long been recognized in Korea. As a result of this issue, Korea is facing a serious socioeconomic crisis. This study explored new and existing policy ideas for overcoming population decline and regional extinction in Korea and explored the importance and effectiveness of these policies in pan-tourism aspects using OpenAI's ChatGPT. Design/methodology/approach: Variables were extracted from existing research papers, reports, journals, and interviews with experts in related fields. The study then examined how ChatGPT recognizes (evaluates) the importance and effectiveness of individual policies or ideas in five fields. This study attempted to increase reliability by taking measurements eight times over one year. Findings: The findings highlighted the prioritization of general strategies such as quality employment, education, healthcare, and housing, alongside the effectiveness of pan-tourism strategies in addressing regional depopulation. Public relations and marketing activities were also deemed crucial, followed by policy development and administrative support. Research limitations/implications: This study is highly significant as it explored short-term and effective policies for overcoming the population decline crisis and regional extinction from a pan-tourism perspective and evaluated these policies using ChatGPT. To ensure the validity of the results, comparative research with stakeholders will be necessary. Originality/value: This study focused on the issues of population decline and regional extinction in Korea, innovatively utilizing ChatGPT for auxiliary analysis. The research findings offer valuable insights for policymakers and professionals involved in regional development and tourism management.
Keywords: 650; Population decline; Regional extinction; ChatGPT; Pan-tourism; Exploratory study